Evidence for seasonal cycles in deep‐sea fish abundances: A great migration in the deep SE Atlantic?. Issue 7 (11th April 2020) - Milligan, Rosanna J.; Scott, E. Marian; Jones, Daniel O. B.; Bett, Brian J.; Jamieson, Alan J.; O'Brien, Robert; Pereira Costa, Sofia; Rowe, Gilbert T.; Ruhl, Henry A.; Smith, Ken L.; de Susanne, Philippe; Vardaro, Michael F.; et al.
Abstract: Animal migrations are of global ecological significance, providing mechanisms for the transport of nutrients and energy between distant locations. In much of the deep sea (>200 m water depth), the export of nutrients from the surface ocean provides a crucial but seasonally variable energy source to seafloor ecosystems. Seasonal faunal migrations have been hypothesized to occur on the deep seafloor as a result, but have not been documented. Here, we analyse a 7.5‐year record of photographic data from the Deep‐ocean Environmental Long‐term Observatory Systems seafloor observatories to determine whether there was evidence of seasonal (intra‐annual) migratory behaviours in a deep‐sea fish assemblage on the West African margin and, if so, identify potential cues for the behaviour. Our findings demonstrate a correlation between intra‐annual changes in demersal fish abundance at 1, 400 m depth and satellite‐derived estimates of primary production off the coast of Angola. Highest fish abundances were observed in late November with a smaller peak in June, occurring approximately 4 months after corresponding peaks in primary production. Observed changes in fish abundance occurred too rapidly to be explained by recruitment or mortality, and must therefore have a behavioural driver. Given the recurrent patterns observed, and the established importance of bottom‐up trophic structuring in deep‐sea ecosystems, we hypothesize that a large fraction of the fish assemblage may conduct seasonal migrations in this region, and propose seasonal variability in surface ocean primary production as a plausible cause. Such trophic control could lead to changes in the abundance of fishes across the seafloor by affecting secondary production of prey species and/or carrion availability for example. In summary, we present the first evidence for seasonally recurring patterns in deep‐sea demersal fish abundances over a 7‐year period, and demonstrate a previously unobserved level of dynamism in the deep sea, potentially mirroring the great migrations so well characterized in terrestrial systems. Abstract : The authors demonstrate a significant correlation between epipelagic primary production and deep‐sea fish abundances at 1, 500 m from 2010 to 2016 on the Angola margin. These findings highlight the importance of upper‐ocean processes to deep‐sea ecosystem functioning, and their potential vulnerability to future change. Abstrata: As migrações dos animais são importantes para a ecologia global pois fornecem mecanismos para o transporte de nutrientes e energia entre diferentes locais. Em grande parte do oceano profundo (>200 m de profundidade), a exportação de nutrientes da superfície para os ecossistemas do fundo marinho é uma fonte de energia crucial, mas que varia entre estações. Consequentemente, calcula-se que ocorram migrações sazonais de animais no fundo marinho, mas tal nunca foi reportado. Neste estudo, nós analisamos dados fotográficos do observatório do fundo marinho DELOS colhidos ao longo de 7.5 anos, para determinar se existem indícios de comportamentos migratórios sazonais (intra-anuais) na comunidade de peixes de profundidade na costa oeste africana ao largo de Angola e, se se confirmar, tentar identificar o que desencadeia este comportamento. Os resultados obtidos mostram que há uma correlação entre as alterações intra-anuais da densidade de peixes demersais a 1, 400 m de profundidade e as estimativas de produção primária obtidas por satélite. A densidade de peixes atinge o seu máximo no final de Novembro, com um pico menos acentuado em Junho, aproximadamente quatro meses após os respectivos picos de produção primária na superfície. As alterações na densidade de peixe ocorreram de uma forma tão rápida que não podem ser explicadas por recrutamento ou mortalidade, e como tal devem só podem ser geradas por uma alteração do comportamento. Dado a recorrência do padrão observado, e importância da estrutura trófica fundo-topo em ecossistemas do oceano profundo, nós colocamos a hipótese de que uma fracção grande da comunidade de peixes faz migrações sazonais nesta região, e propomos que a variação sazonal da produção primária na superfície esteja na sua origem. Este controlo trófico poderá levar a alterações na densidade de peixes no fundo marinho via, por exemplo, a produção secundária de presas e/ou disponibilidade de corpos em processo de decomposição. Resumindo, nós apresentamos aqui a primeira evidência de padrões sazonais recorrentes na densidade de peixes demersais de profundidade ao longo de um período de sete anos, e provamos existir um nível de dinamismo nunca dantes observado no oceano profundo, que poderá espelhar as grandes migrações comummente observadas em sistemas terrestres.